Glycoglycerolipids From Sargassum vulgare as Potential Antifouling Agents - Plouguerné, Erwan; de Souza, Lauro M.; Sassaki, Guilherme L.; Hellio, Claire; Trepos, Rozenn; da Gama, Bernardo A. P.; Pereira, Renato Crespo; Barreto-Bergter, Eliana (Frontiers in Marine Science, 2020)
Unravelling new environmentally friendly antifouling (AF) agents is one of the major quests currently facing marine biotechnology. Marine macroalgae represent a rich source of new compounds with promising biological properties, including AF activity, but most of the macroalgal compounds studied to date are terpenoids or polyphenolics. The aim of this work was to investigate the possible AF role played by a usually neglected class of marine natural products: glycolipids (monogalactosyldiacylglycerols - MGDG, digalactosyldiacylglycerols – DGDG and sulfoquinovosyldiacylglycerols - SQDG) isolated from the Phaeophyceae Sargassum vulgare collected along the coast of south-eastern Brazil. Among the 18 extracts, fractions and sub-fractions tested, 3 sub-fractions demonstrated particularly promising AF activity towards the growth inhibition of marine bacteria and microalgae: F3III117, F4II70a and F4II70b. The main compounds present in these fractions were identified as MGDG, DGDG, and SQDG, respectively. These results highlight the potential of glycoglycerolipids from S. vulgare as new promising antifouling agents.